2018
DOI: 10.1111/tri.13311
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience of sequential use of normothermic and hypothermic oxygenated perfusion for donation after circulatory death kidney with warm ischemia time over the conventional criteria - a retrospective and observational study

Abstract: Donation after circulatory death (DCD) is a potential source of reducing organ demand. In Italy, DCD requires a 20-min no-touch period that prolongs warm ischemia and increases delayed graft function (DGF) risk and graft loss. We report here our preliminary experience of sequential use of normothermic regional perfusion (NRP), as standard procedure, and hypothermic oxygenated perfusion (HOPE), as an experimental technique of organ preservation, in 10 kidney transplants (KT) from five DCD Maastricht III with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…We had a previous experience of normothermic perfusion and ex-vivo HOPE for DCD kidneys with good result [44], but to the best of our knowledge, this is the first case to be reported in Italy of AKI in DCD kidney with prolonged warm ischemic time due to 20 min'no-touch' period (as per the Italian law), and with a worse creatinine level during NRP, but which was successfully transplanted with after ex-vivo HOPE.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We had a previous experience of normothermic perfusion and ex-vivo HOPE for DCD kidneys with good result [44], but to the best of our knowledge, this is the first case to be reported in Italy of AKI in DCD kidney with prolonged warm ischemic time due to 20 min'no-touch' period (as per the Italian law), and with a worse creatinine level during NRP, but which was successfully transplanted with after ex-vivo HOPE.…”
Section: Discussionmentioning
confidence: 90%
“…Oxygen delivery during hypothermic preservation (HOPE), also called hypothermic oxygenated perfusion prevents hypoxic injury [22] by increasing adenosine triphosphate content [23]. Although results obtained from preclinical studies are promising [24][25][26], only a few clinical trials have evaluated oxygenation during HMP in kidney transplantation [27][28][29] and some trials are ongoing [30]. The development of modern organ preservation techniques have enabled to overcome the restrictions imposed by law related to the prolonged warm ischemia time; the Italian practice for DCD involves starting the regional normothermic perfusion immediately after death declaration, followed by ex-vivo machine perfusion (hypothermic or normothermic) [2,3,31].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is only partial evidence that post-transplant infection risk could be higher in DCD kidney transplants compared to the DBD ones [4,8,9]. In order to reduce complications related to longer warm and cold ischemia times, the DCD donor management is very complex and must be fast, due to the need of maintaining circulation during organ retrieval and of pre-implantation machine perfusion of organs [6,8]. All of these steps represent possible contamination sources, that add to the already known potential infectious risk of the donor [10].…”
Section: Discussionmentioning
confidence: 99%
“…No antibiotic therapy was performed. After three hours of extracorporeal membrane oxygenation (ECMO), the graft was treated ex-vivo with hypothermic oxygenated machine perfusion for 90 min, as of our center practice [6]. Pre-implantation biopsy reported a total Karpinsky score of 2 (interstitial fibrosis: 1, vascular disease: 1).…”
Section: Introductionmentioning
confidence: 99%
“…Ravaioli et al have recently published a series of 10 kidneys from controlled DCD donors using NRP and HOPE. The authors reported a delayed graft function rate of 30% but no cases of primary non-function [13].…”
mentioning
confidence: 95%